2005
DOI: 10.1029/2004ja010888
|View full text |Cite
|
Sign up to set email alerts
|

Neutral atmospheric influences of the solar proton events in October–November 2003

Abstract: [1] The large solar storms in October-November 2003 caused solar proton events (SPEs) at the Earth and impacted the middle atmospheric polar cap regions. Although occurring near the end of the maximum of solar cycle 23, the fourth largest period of SPEs measured in the past 40 years happened 28-31 October 2003. The highly energetic protons associated with the SPEs produced ionizations, excitations, dissociations, and dissociative ionizations of the background constituents, which led to the production of odd hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
232
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 185 publications
(254 citation statements)
references
References 49 publications
20
232
2
Order By: Relevance
“…SPE-caused NO x increases have been shown in several studies (e.g., McPeters, 1986;Zadorozhny et al, 1992Zadorozhny et al, , 1994Randall et al, 2001;López-Puertas et al, 2005a;Jackman et al, 1995Jackman et al, , 2005bJackman et al, , 2008Jackman et al, , 2011Jackman et al, , 2014Funke et al, 2011;Friederich et al, 2013). Other NO y constituents like HNO 3 , HNO 4 , N 2 O 5 , and ClONO 2 (e.g., López- Puertas et al, 2005b;Jackman et al, 2008;Funke et al, 2011;Damiani et al, 2012; as well as the total NO y family (e.g., Funke et al, 2011Funke et al, , 2014a have also been shown to increase as a result of large SPEs.…”
Section: Solar Protonsmentioning
confidence: 97%
See 2 more Smart Citations
“…SPE-caused NO x increases have been shown in several studies (e.g., McPeters, 1986;Zadorozhny et al, 1992Zadorozhny et al, , 1994Randall et al, 2001;López-Puertas et al, 2005a;Jackman et al, 1995Jackman et al, , 2005bJackman et al, , 2008Jackman et al, , 2011Jackman et al, , 2014Funke et al, 2011;Friederich et al, 2013). Other NO y constituents like HNO 3 , HNO 4 , N 2 O 5 , and ClONO 2 (e.g., López- Puertas et al, 2005b;Jackman et al, 2008;Funke et al, 2011;Damiani et al, 2012; as well as the total NO y family (e.g., Funke et al, 2011Funke et al, , 2014a have also been shown to increase as a result of large SPEs.…”
Section: Solar Protonsmentioning
confidence: 97%
“…The ozone response due to very large SPEs is fairly rapid and substantial and has been observed during and after numerous events to date (e.g., Weeks et al, 1972;Heath et al, 1977;McPeters et al, 1981;Thomas et al, 1983;Solomon et al, 1982;McPeters and Jackman, 1985;Jackman et al, 1990Jackman et al, , 1995Jackman et al, , 2001Jackman et al, , 2005bJackman et al, , 2008Jackman et al, , 2011Jackman et al, , 2014 Decreases in mesospheric and upper stratospheric ozone are mostly caused by SPE-induced HO x increases, which were predicted to occur over 42 years ago (e.g., see Swider and Keneshea, 1973). Direct measurements of SPE-caused OH and HO 2 enhancements have confirmed these early predictions (e.g., Damiani et al, 2008;Jackman et al, 2011Jackman et al, , 2014).…”
Section: Solar Protonsmentioning
confidence: 99%
See 1 more Smart Citation
“…As SEPs penetrate into the collisional atmosphere, they ionize neutrals along the way, greatly enhancing the electrical conductivity [Holzworth and Mozer, 1979;Holzworth et al, 1987]. Enhanced conductivity can cause communication disruptions (radio, GPS, avionics [Jones et al, 2005]) and can have significant impacts on atmospheric chemistry [Jackman et al, 2005;Verronen et al, 2005]. Under normal fair weather circumstances, the largest vertical electric fields in the atmosphere arise from the global electric circuit (GEC) [Wilson, 1920].…”
Section: Introductionmentioning
confidence: 99%
“…In the present work our scheme was updated to produce 1.25 odd nitrogen atoms per ion pair produced by cosmic rays, according to Jackman et al (1980), based on calculations of dissociation branching ratios from relativistic particle impact cross sections (Porter et al 1976). We introduced a parameterization whereby the GCR-induced N-production was split into two channels, i.e 45% ground-state N and 55% excited-state N (see Jackman et al 2005, and references therein). We also introduced an energydependence to the total N 2 ionization cross section by electron impact (Tabataba-Vakili et al 2016), replacing the constant electron impact cross section of 1.75 × 10 −16 cm 2 previously used with the energy-dependent cross section of Itikawa (2006).…”
Section: Cosmic-ray Schemementioning
confidence: 99%